Main results of the European PASSAM project on severe accident source term mitigation. (June 2018) - Albiol, T.; Herranz, L.; Riera, E.; Dalibart, C.; Lind, T.; Del Corno, A.; Kärkelä, T.; Losch, N.; Azambre, B.; Mun, C.; Cantrel, L.
Highlights: The PASSAM European Project investigated filtered containment venting systems (FCVS) It provided an extended database on mitigation systems for severe nuclear accidents. It highlighted the risk of delayed released of trapped radioactive iodine species. Hydrodynamic and trapping phenomena in pool scrubbers were studied. Zeolites showed their high capacity for organic iodine trapping. Abstract: The PASSAM (Passive and Active Systems on Severe Accident source term Mitigation) project was launched in the frame of the 7th framework programme of the European Commission. Coordinated by IRSN, this four year project (2013–2016) involved nine partners from six countries: IRSN, EDF and university of Lorraine (France); CIEMAT and CSIC (Spain); PSI (Switzerland); RSE (Italy); VTT (Finland) and AREVA GmbH (Germany). It was mainly an R&D project of experimental nature aimed at investigating phenomena that might enhance source term mitigation in case of a severe accident in a Nuclear Power Plant (NPP). Both existing systems (i.e., water scrubbing and sand bed filters plus metallic pre-filters) and innovative ones (i.e., high pressure sprays, electrostatic precipitators, acoustic agglomerators and, advanced zeolites and combined wet-dry filtration systems), were experimentally studied in conditions as close as possible from those anticipated for severe accidents. This paper presents the main experimental results of the project which represent a significant extension of the current database on these existing or innovative mitigation systems. Application of some of these data for improving existing models or developing new ones should eventually enhance the capability of modelling Severe Accident Management measures and developing improved guidelines.